Non-muscle invasive bladder cancer risk stratification - Isharwal, Sumit; Konety, Badrinath (Indian journal of urology, 2015)
Non-muscle invasive bladder cancer (NMIBC) comprises about 70% of all newly diagnosed bladder cancer, and includes tumors with stage Ta, T1 and carcinoma in situ (CIS.) Since, NMIBC patients with progression to muscle-invasive disease tend to have worse prognosis than with patients with primary muscle-invasive disease, there is a need to significantly improve risk stratification and earlier definitive treatment for high-risk NMIBC. A detailed Medline search was performed to identify all publications on the topic of prognostic factors and risk predictions for superficial bladder cancer/NMIBC. The manuscripts were reviewed to identify variables that could predict recurrence and progression. The most important prognostic factor for progression is grade of tumor. T category, tumor size, number of tumors, concurrent CIS, intravesical therapy, response to bacillus Calmette-Guerin at 3- or 6-month follow-up, prior recurrence rate, age, gender, lymphovascular invasion and depth of lamina propria invasion are other important clinical and pathological parameters to predict recurrence and progression in patients with NMIBC. The European Organization for Research and Treatment of Cancer (EORTC) and the Spanish Club UrológicoEspañol de Tratamiento Oncológico (CUETO) risk tables are the two best-established predictive models for recurrence and progression risk calculation, although they tend to overestimate risk and have poor discrimination for prognostic outcomes in external validation. Molecular biomarkers such as Ki-67, FGFR3 and p53 appear to be promising in predicting recurrence and progression but need further validation prior to using them in clinical practice. EORTC and CUETO risk tables are the two best-established models to predict recurrence and progression in patients with NMIBC though they tend to overestimate risk and have poor discrimination for prognostic outcomes in external validation. Future research should focus on enhancing the predictive accuracy of risk assessment tools by incorporating additional prognostic factors such as depth of lamina propria invasion and molecular biomarkers after rigorous validation in multi-institutional cohorts.